Hubungan Antara Kepercayaan Konsumen Dengan Kepuasan Konsumen Mahasiswa Fakultas Psikologi Pengguna Smartphone Iphone Di Universitas Muhammadiyah Surakarta - Kusuma, Rezha Restya, Susatyo Yuwono, S.Psi, M.Si.,Psi (2017)
This study aims to determine the relationship between consumer confidence with consumer satisfaction iPhone smartphone users. The hypothesis in this study is "There is a positive relationship between consumer confidence with satisfaction Student Faculty of Psychology iPhone smartphone users at the University of Muhammadiyah Surakarta". The subject of this research is 154 students of Faculty of Psychology University of Muhammadiyah Surakarta using iPhone smartphone product. The data collection method used in this research is using the scale of customer satisfaction and consumer trust scale. Method using quantitative approach with measuring scale of consumer satisfaction and consumer satisfaction. Data analysis technique used in this research is Non-Parametric correlation of Spearman by using SPSS 16 For Windows program. Based on the result from data analisys, obtained correlation coefficient of 0.371 significance 0,000; (P <0.001) which means there is a positive or significant relationship between consumer confidence with consumer satisfaction iPhone smartphone users. Effective contribution or the role of consumer confidence in consumer satisfaction of 13.8%, the remaining 86.2% influenced by other factors. The consumer confidence variable has empirical average of 70.31 so it has a category that is high, and while consumer confidence variable of iPhone smartphone user has empirical average 64,66 so it has category which is classified as being. Keyword : consumer trust, consumer satisfaction, smartphone iPhone